Development of fluorescent reverse transcription loop-mediated isothermal amplification (RT-LAMP) using quenching probes for the detection of the Middle East respiratory syndrome coronavirus - Shirato, Kazuya; Semba, Shohei; El-Kafrawy, Sherif A.; Hassan, Ahmed M.; Tolah, Ahmed M.; Takayama, Ikuyo; Kageyama, Tsutomu; Notomi, Tsugunori; Kamitani, Wataru; Matsuyama, Shutoku; Azhar, Esam Ibraheem (Journal of virological methods, 2018)
•Fluorescent RT-LAMP assays using quenching probes for MERS-CoV were developed.•Quenching probe (QProbe) can solve the problem in turbidity monitoring mechanism.•Only primer-derived signal can be monitored specifically by QProbes.•Two primer sets were developed to enable to confirm MERS case by RT-LAMP only.•Both sets were highly specific and sensitive in comparison with real-time RT-PCR. Clinical detection of Middle East respiratory syndrome (MERS) coronavirus (MERS-CoV) in patients is achieved using genetic diagnostic methods, such as real-time RT-PCR assay. Previously, we developed a reverse transcription-loop-mediated isothermal amplification (RT-LAMP) assay for the detection of MERS-CoV [Virol J. 2014. 11:139]. Generally, amplification of RT-LAMP is monitored by the turbidity induced by precipitation of magnesium pyrophosphate with newly synthesized DNA. However, this mechanism cannot completely exclude the possibility of unexpected reactions. Therefore, in this study, fluorescent RT-LAMP assays using quenching probes (QProbes) were developed specifically to monitor only primer-derived signals. Two primer sets (targeting nucleocapsid and ORF1a sequences) were constructed to confirm MERS cases by RT-LAMP assay only. Our data indicate that both primer sets were capable of detecting MERS-CoV RNA to the same level as existing genetic diagnostic methods, and that both were highly specific with no cross-reactivity observed with other respiratory viruses. These primer sets were highly efficient in amplifying target sequences derived from different MERS-CoV strains, including camel MERS-CoV. In addition, the detection efficacy of QProbe RT-LAMP was comparable to that of real-time RT-PCR assay using clinical specimens from patients in Saudi Arabia. Altogether, these results indicate that QProbe RT-LAMP assays described here can be used as powerful diagnostic tools for rapid detection and surveillance of MERS-CoV infections.